Analysis of Chinese competitive sports development characteristics at the 25th to 28th Olympic Games - Wang, J.; Lai, Q.; Tian, H. (The 8th Asia Conference on Kinesiology, 2017)
China`s achievement in the Olympic Games is evidenced in the development level of competitive sports. Previous research revealed that various factors have influenced the progression and trend of competitive sports development. However, limits to the Chinese competitive sports development characteristics have been an issue of topical interest. The purposes of the present study were: to determine the factors influencing the Chinese competitive sports development, to analysis the Chinese competitive sports events` distribution from the 25th to 28th Olympic Games. [Methods] Coaches, administers and eleven athletes who participated in from the 25th to 28th Olympic Games were interviewed. Interviews were conducted using semi-structured and open-ended approach (Durand-Bush, 2010). The sports events distributions were evaluated with Olympic video recordings. The data were analysed qualitatively and quantitatively. [Results] The results showed that China`s priority sports, such as gymnastics, table tennis, badminton, shooting and swimming, during the past four Olympic Games presented to be stationary and equilibrium major factors including the lack of personal training and technical innovations, coaching issues, overtraining and injury, as well as insufficient funding, negatively influenced the Chinese competitive sports development. [Discussion] It was concluded that Chinese competitive sports have been highly observed and motivated to win gold medals in priority sports events, which presented to be stationary and equilibrium. Further research, including improvements in sport technology, development and maintenance of expert athletic performance, as well as increasing in financial support, are highly needed.